Acute pancreatitis as a complication of dengue fever - Ridho, Sayid (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2000)
Acute pancreatitis is a rare complication of dengue fever that usually occurs without hyperglycemia. We report one patient of dengue fever with a complication of acute pancreatitis. A 28 year old male was referred from a private clinic to Dr. Cipto Mangunkusumo hospital, because of fever and abdominal pain since two days before admission. The physical examination showed slight fever and epigastric pain. The laboratory examination revealed leukocytosis, thrombocytopenia and increased levels of serum amylase and lypase. The diagnosis of dengue infection was made after the finding the IgM for dengue virus. After 12 days of hospitalization, the patient’s clinical signs and symptoms and laboratory findings were within normal limits.  Key words: acute pancreatitis, dengue fever